Evaluation of Arterial Injury Due to Balloon Angioplasty by 111In-Labelled Platelets - Kadir, S.; Hill-Zobel, R. L.; Tsan, M. F. (Nuklearmedizin - NuclearMedicine, 1983)
The sensitivity of 111In-labelled platelets for the detection of intimai trauma following balloon angioplasty was evaluated in 8 arteries in 6 patients. Focal platelet accumulation was detected at all 3 iliacs, one superficial femoral and the anterior tibial artery angioplasty sites. Minimal platelet accumulation was present at the superficial femoral artery angioplasty site in another patient whereas in both renal arteries no focal platelet accumulation was detectable. These results indicate that 111In-labelled platelets may provide a sensitive method for evaluation platelet accumulation at the balloon angioplasty site in the peripheral circulation.